1930
DOI: 10.3382/ps.0090157
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Studies of the Variations in the Growth of Single Comb White Leghorns and their Significance

Abstract: Economical poultry flock management requires early selection of those individuals that are to be used for flock replacement. The weight of the individual is considered of primary importance in this selection. A study of the variations in growth and their relationship at different ages should improve the available knowledge in regard to early selection. A measurement of variation in growth should also prove valuable in future investigations.REVIEW OF LITERATURE Very few studies of this nature have been made and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1930
1930
1955
1955

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In the first place, chick weight at hatching appears to bear no relation to subsequent weights at either 3, 8, or 16 weeks of age or to weight at sexual maturity. These findings are in general agreement with those previously reported for smaller numbers of individuals of the same strain of White Leghorns by Funk, Knandel, and Callenbach (1930). They also agree with the conclusions of Upp (1928) working with Rhode Island Reds, Latimer (1924) working with White Leghorns, and in part with Heuser and Andrews (1932) working with White Leghorns and mixed heavy breeds.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…In the first place, chick weight at hatching appears to bear no relation to subsequent weights at either 3, 8, or 16 weeks of age or to weight at sexual maturity. These findings are in general agreement with those previously reported for smaller numbers of individuals of the same strain of White Leghorns by Funk, Knandel, and Callenbach (1930). They also agree with the conclusions of Upp (1928) working with Rhode Island Reds, Latimer (1924) working with White Leghorns, and in part with Heuser and Andrews (1932) working with White Leghorns and mixed heavy breeds.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…Statistical studies of the growth of White Leghorns by Funk, Knandel, and Callenbach (1930) show that the coefficient of variability may be as large as 19.4 at four weeks of age and that it varies from 14.6 to 19.4 in four different broods. At 16 weeks they found less variability of the individual weights, but between the heaviest and the lightest chicks, within each of the four broods, there were differences varying from a little less than one pound to one and threefourths pounds.…”
mentioning
confidence: 98%
“…Body weight was taken in pounds at the end of the first, second, third, and fourth month of age. Funk, Knandel, and Callenbach (1930) found that initial chick weights and subsequent weights showed little correlation but that weights at 4, 8, 16, and 24 weeks show a high positive correlation with each other.…”
Section: Methods Of Proceduresmentioning
confidence: 92%